Longyearbyen CO2 lab project—from a vision of a CO2-neutral Svalbard to a geoscience data eldorado - Kim Senger; Peter Betlem; Alvar Braathen; Snorre Olaussen; Gunnar Sand (Arctic Science)
The Longyearbyen CO2 lab project was initiated in 2006 by the University Centre in Svalbard (UNIS) to establish whether subsurface storage of locally produced CO2 is feasible. Over a decade of drilling operations and geoscientific research concluded that the subsurface was suitable for storing the CO2 generated from the local power plant. The geological ingredients for successful CO2 storage are in place, comprising a ca. 300 m thick, sandstone-dominated reservoir rock capped by an impermeable mudstone-dominated succession. No CO2 was ever injected for storage in Svalbard for economic and political reasons. However, the project generated a wealth of new data, some of which proved critical for studies related to CO2 storage elsewhere. The data were also key to the characterization of fluid flow and geothermal potential in Svalbard, deciphering past climatic changes, unravelling past tectonic events, some of relevance for understanding the plate tectonic evolution of the Arctic, as well as updating the global geological timescale. In this contribution, we briefly outline the history and main achievements of the Longyearbyen CO2 lab project, before describing, categorizing and openly sharing the publicly available data from the project, including peer-reviewed publications (123 so far) and theses (18 PhD and 34 MSc).